Pengembangan Panduan Layanan Informasi Pencegahan Pelecehan Seksual (Menggunakan Pendekatan Contextual Teaching And Learning - Sulistyawati, Nurwinda; Alfath, Annajmi (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2024)
This research aims to develop a sexual harassment prevention information service guide (using a Contextual Teaching and Learnong approach). Using the AADIE model development research method (Analyze, Design, Development, Implementation and Evaluation), with small group research subjects consisting of 3 experts and 3 guidance and counseling teachers. The research results show that the sexual harassment prevention information service guide is valid and can be used by guidance and counseling teachers to improve the prevention of sexual harassment.